Penerapan Model Belajar Quantum Teaching Terhadap Hasil Belajar Mata Pelajaran IPS - Adella Refrina Chusnul Chotimah; Dian Alfia Purwandari; Nova Scorviana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This study aims to determine the impact of the application of the Quantum Teaching learning model on student learning outcomes. The research method used is Classroom Action Research (CAR). Data was collected by giving multiple choice post test questions and observation sheets for teacher and student activities. The results of the study by applying the Quantum Teaching learning model showed that there was an increase in student learning outcomes by 15% from cycle 1 to cycle 2, as well as an increase in the average value of learning from 77 to 87 which had reached the target of Achievement Indicators (IPH) ?80 % of KKM 78. The application of the Quantum Teaching learning model has also succeeded in increasing the activity of students in the aspects of asking, answering, arguing, and collaborating. The activeness of the participants in cycle 1 was dominated by the less active category, but in cycle 2 there was a decrease in that category and there was an increase in the quite active and active category. In addition, in cycle 2 there were students who were very active in the aspects of asking, answering, and giving opinions.